Determination of mesenchymal stem cell fate by pigment epithelium‐derived factor (PEDF) results in increased adiposity and reduced bone mineral content. Issue 11 (25th July 2013) - Gattu, Arijeet K.; Swenson, E. Scott; Iwakiri, Yasuko; Samuel, Varman T.; Troiano, Nancy; Berry, Ryan; Church, Christopher D.; Rodeheffer, Matthew S.; Carpenter, Thomas O.; Chung, Chuhan
Abstract : Pigment epithelium‐derived factor (PEDF), the protein product of the SERPINF1 gene, has been linked to distinct diseases involving adipose or bone tissue, the metabolic syndrome, and osteogenesis imperfecta (OI) type VI. Since mesenchymal stem cell (MSC) differentiation into adipocytes vs . osteoblasts can be regulated by specific factors, PEDF‐directed dependency of murine and human MSCs was assessed. PEDF inhibited adipogenesis and promoted osteoblast differentiation of murine MSCs, osteoblast precursors, and human MSCs. Blockade of adipogenesis by PEDF suppressed peroxisome proliferator‐activated receptor‐γ (PPARγ), adiponectin, and other adipocyte markers by nearly 90% compared with control‐treated cells ( P <0.001). Differentiation to osteoblasts by PEDF resulted in a common pathway that involved PPARγ suppression ( P <0.01). Canonical Wnt‐β‐catenin signaling results in a MSC differentiation pattern analogous to that seen with PEDF. Thus, adding PEDF enhanced Wnt‐β‐catenin signal transduction in human MSCs, demonstrating a novel Wnt agonist function. In PEDF knockout (KO) mice, total body adiposity was increased by >50% compared with controls, illustrating its systemic role as a negative regulator of adipogenesis. Bones from KO mice demonstrated a reduction in mineral content recapitulating the OI type VI phenotype. These results demonstrate that the human diseases associated with PEDF reflect its ability to modulate MSC differentiation.—Gattu, A. K., Swenson, E. S., Iwakiri, Y., Samuel, V. T., Troiano, N., Berry, R., Church, C. D., Rodeheffer, M. S., Carpenter, T. O., Chung, C. Determination of mesenchymal stem cell fate by pigment epithelium‐derived factor (PEDF) results in increased adiposity and reduced bone mineral content. FASEB J . 27, 4384–4394 (2013). www.fasebj.org